Method for improving magnetic performance consistency and corrosion resistance of neodymium iron boron
By spraying Dy or Tb alloy powder and fluoride powder on the sintered NdFeB magnet and heat treatment to form a core-shell structure, the problem that coercive force consistency and corrosion resistance of NdFeB magnets are difficult to meet at the same time. It achieves performance improvement and savings in heavy rare earth usage.
Patent Information
- Application Number
- CN202411758243.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-14
AI Technical Summary
The existing neodymium iron boron magnets have difficult production requirements to meet simultaneously in improving coercive consistency and corrosion resistance. Especially during high-temperature diffusion, the oxidation uneven Dy/Tb alloy powder leads to poor coercive consistency. The fluoride coating damages the magnet surface and reduces corrosion resistance.
The core-shell structure is formed to improve coercive consistency and corrosion resistance by uniformly spraying Dy or Tb alloy powder on the orientation plane of the sintered NdFeB magnet.
The coercive force consistency and corrosion resistance of neodymium iron boron magnets are achieved while improving, reducing the amount of heavy rare earths, and improving on the basis of existing processes, simplifying the changes in equipment and process parameters.
Smart Images

Figure BDA0005166892100000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sintered NdFeB rare earth permanent magnet materials, in particular to a method for improving the magnetic property consistency and corrosion resistance of NdFeB. Background Art
[0002] With the increasing demand for high-performance NdFeB permanent magnet materials in many fields such as computers, communications, automatic control, energy, transportation, electronics, home appliances, office automation, hybrid vehicles, etc. In recent years, with the rapid development of industries such as hybrid vehicles and new energy, higher requirements have been placed on the temperature stability and high remanence characteristics of magnets. In traditional processes, more heavy rare earth elements are added during the smelting process to increase the coercivity of the magnet and thus improve the temperature characteristics. However, due to the heavy rare earth (Dy / Tb)2Fe 14 The low saturation magnetization intensity of B leads to a decrease in remanence and magnetic energy product. At the same time, the high price of heavy rare earths limits the application of high-performance magnets, which is not conducive to the development of downstream industries.
[0003] In recent years, a grain boundary diffusion method has been developed, that is, a metal powder, fluoride or alloy deposition layer containing heavy rare earth Dy / Tb is formed on the surface of NdFeB magnets by spraying, magnetron sputtering deposition, screen printing, etc., and then the Dy / Tb element is diffused along the low melting point grain boundary and enters the internal area of the magnet by heat treatment, and is concentrated on the surface of the main phase grains to form the so-called core-shell structure, so that the epitaxial layer of the main phase grains is magnetically hardened, thereby greatly improving the coercive force with very little heavy rare earth without significantly reducing the remanence, and preparing low-cost and high-performance sintered NdFeB magnets, and even breaking through the performance limit of traditional preparation processes. At present, two technologies are widely used, namely, coating Dy / Tb alloy powder or coating Dy / Tb fluoride powder. Since the coated Dy / Tb alloy powder is easily oxidized, it is inevitable that the oxidation degree of Dy / Tb alloy powder on the surface of the magnets at different positions in the same box is different during the high-temperature diffusion process of large-scale production. That is, the surface oxidation of the magnets stacked on the surface of the box is more serious than that of the lower magnets, resulting in inconsistent total amount of heavy rare earth entering the magnet, resulting in poor consistency of coercive force. Fluoride will cause very serious damage to the surface of the magnet, which will cause the corrosion resistance of the magnet to deteriorate and cannot be used in high-end industries. In summary, how to ensure the consistency of magnet performance, save the amount of heavy rare earth, and improve the corrosion resistance of the magnet has become one of the key research directions of the industry. Therefore, a method to improve the consistency and corrosion resistance of NdFeB magnetic properties is urgently needed to solve this problem. Summary of the invention
[0004] The object of the present invention is to provide a method for improving the consistency of magnetic properties and corrosion resistance of NdFeB magnets, so as to solve the problem that the consistency of coercive force and corrosion resistance of NdFeB magnets are difficult to meet production requirements at the same time.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for improving the magnetic property consistency and corrosion resistance of NdFeB, comprising the following specific contents: uniformly spraying alloy powder of Dy and / or Tb on two orientation planes of a prepared sintered NdFeB magnet, and then uniformly spraying fluoride powder of Dy and / or Tb on two orientation planes of the sintered NdFeB magnet after spraying the alloy powder, and obtaining a NdFeB magnet product by heat treatment.
[0006] Preferably, the amount of alloy powder is M*m*X% / n, and the amount of fluoride powder is M*m*(1-X%) / n, wherein M is the total weight of the prepared sintered NdFeB magnet, n is the mass ratio of Dy and Tb elements in the alloy powder used, m is 0.2-1%, and X is 0-70.
[0007] Preferably, m is 0.5%, X is not greater than 70, and the difference between the maximum and minimum coercive force of the obtained NdFeB magnet product is less than 0.3 kOe.
[0008] Preferably, m is 0.5%, X is not less than 50, and the weight loss of the obtained NdFeB magnet product is less than 0.3 mg / cm under the standard conditions of 2.6 atmospheres, 95% humidity, 130°C, and 240h. 2 .
[0009] Preferably, the alloy powder of Dy and / or Tb is Dy 73.6 Cr5Si5Al7Cu 9.4 or / and Tb 73.6 Cr5Si5Al7Cu 9.4 , with an average particle size of 2 to 8 μm; the fluoride powder of Dy and / or Tb uses DyF3 / TbF3, with an average particle size of 1.5 to 3 μm.
[0010] Preferably, the alloy powder and fluoride powder are sprayed by mixing the powder and anhydrous ethanol in a ratio of 1 kg powder to 2 L anhydrous ethanol to form a slurry and then spraying.
[0011] Preferably, the heat treatment includes neatly stacking the sprayed magnets into a graphite sintering box, keeping the temperature at 850-940°C for 12-20 hours, rapidly cooling the temperature to below 80°C with argon, heating the temperature to 480-540°C again, keeping the temperature for 3-5 hours, and rapidly cooling the temperature to below 80°C with argon.
[0012] Preferably, the preparation steps of the prepared sintered NdFeB magnet include: after being machined into a desired size and shape, cleaning the surface oxide layer, and drying for standby use.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The method for improving the consistency and corrosion resistance of NdFeB magnetic properties has simple steps and is easy to operate. Based on the existing NdFeB magnet preparation process, there is not much modification, and only the spraying of two materials is added in the middle. Therefore, the existing equipment and process parameters do not need to be changed, which is conducive to the transformation and implementation of production. After adopting the method of the present invention, the prepared product can not only have good coercive force consistency, but also excellent corrosion resistance, and the amount of heavy rare earth used is relatively small. The present invention can further improve the consistency and corrosion resistance of the product on the basis of the performance of the existing sintered NdFeB magnet itself. DETAILED DESCRIPTION
[0015] The core of the present invention is: uniformly spraying Dy or / and Tb alloy powder on the two orientation planes of the prepared sintered NdFeB magnet, then uniformly spraying Dy or / and Tb fluoride powder on the two orientation planes of the sintered NdFeB magnet after the alloy powder is sprayed, and finally heat treating. Through this method, a NdFeB magnet product with good coercive force consistency and excellent corrosion resistance can be obtained.
[0016] In a preferred embodiment, the amount of alloy powder is M*m*X% / n, and the amount of fluoride powder is M*m*(1-X%) / n, wherein M is the total weight of the prepared sintered NdFeB magnet, n is the mass ratio of Dy and Tb elements in the alloy powder used, m is 0.2-1%, and X is 0-70;
[0017] For the above preferred solutions, the m value currently adopted by the industry with a relatively high cost performance is 0.5%, which is not only conducive to the conservation of rare earth resources, but also can obtain better product performance; on this basis, it is further preferred that when X is not greater than 70, the difference between the maximum and minimum coercive force of the obtained NdFeB magnet product is less than 0.3kOe, and better product consistency can be obtained; on this basis, it is further preferred that when X is not less than 50, the obtained NdFeB magnet product can obtain better corrosion resistance, and under the standard conditions of 2.6 atmospheres, 95% humidity, 130°C, and 240h, the weight loss is less than 0.3mg / cm 2 When X is between 50 and 70, a product with both optimal properties can be obtained.
[0018] For reference, the above-mentioned Dy and / or Tb alloy powder can be Dy 73.6 Cr5Si5Al7Cu 9.4 or / and Tb 73.6 Cr5Si5Al7Cu 9.4 The average particle size can be further selected to be 2 to 8 μm; the fluoride powder of Dy and / or Tb can be DyF3 / TbF3, and the average particle size can be further selected to be 1.5 to 3 μm.
[0019] Conventionally, the alloy powder and fluoride powder are sprayed by mixing the powder and anhydrous ethanol in a ratio of 1 kg powder to 2 L anhydrous ethanol to form a slurry and then spraying.
[0020] Conventionally, the heat treatment includes neatly stacking the sprayed magnets into a graphite sintering box, keeping them at 850-940°C for 12-20 hours, rapidly cooling them to below 80°C with argon, heating them again to 480-540°C and keeping them for 3-5 hours, and rapidly cooling them to below 80°C with argon.
[0021] Conventionally, the preparation steps of the prepared sintered NdFeB magnet include: after being machined into the required size and shape, cleaning the surface oxide layer, and drying for use.
[0022] The following comparative examples and embodiments use commercially available N55 sintered NdFeB magnets as raw materials. The magnets themselves have relatively good performance and can produce products with better comprehensive performance. However, this does not mean that only this magnet can be used as a raw material. Different sintered NdFeB magnets such as N50, N52, and N54 can also be used. The specific raw material model does not affect the method of the present invention. Similarly, the following comparative examples and embodiments only use Tb alloys and fluorides to avoid affecting the credibility of parallel experiments. In actual production, Dy elements can be used to partially or completely replace Tb elements on the basis of the following scheme. In addition, the element composition of the specific alloys used and the total amount of alloys and fluorides used are also for parallelism. The specific selection range should be based on the above implementation method.
[0023] Comparative Example 1: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and was machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and then dried with hot air for standby use;
[0024] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (Weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1 kg powder to 2 L anhydrous ethanol to form a slurry for standby use; 0.5% / 73.6% Tb by weight of the magnet is added 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0025] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0026] Comparative Example 2: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and was machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and then dried with hot air for standby use;
[0027] The commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3 μm and anhydrous ethanol are mixed in a ratio of 1 kg powder to 2 L anhydrous ethanol to form a slurry for standby use; 0.5% / 73.6% TbF3 powder is evenly sprayed on two orientation planes of a D10mm*7mm disc magnet;
[0028] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0029] Example 1: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0030] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*20% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-20%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0031] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0032] Example 2: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0033] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*30% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-30%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0034] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0035] Example 3: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0036] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4(weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*40% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on two orientation planes of a D10mm*7mm disc magnet, and further 0.5%*(1-40%) / 73.6% terbium fluoride (TbF3) is evenly sprayed on two orientation planes of a D10mm*7mm disc magnet;
[0037] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0038] Example 4: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0039] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*50% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-50%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0040] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0041] Example 5: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0042] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*60% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-60%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0043] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0044] Example 6: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0045] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4(weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*70% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-70%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0046] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0047] Example 7: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0048] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*80% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-80%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0049] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0050] Example 8: A commercially available N55 sintered NdFeB magnet with a remanence of 14.7 kGs and a coercive force of 13.6 kOe was used, and machined into a D10 mm*7 mm disc magnet, wherein the 7 mm thickness direction is the magnet orientation direction, and then the surface oxide layer was cleaned with a 2% nitric acid solution, and dried with hot air for standby use;
[0051] Tb with an average particle size of 2 to 8 μm 73.6 Cr5Si5Al7Cu 9.4 (weight percentage) alloy powder and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; commercially available terbium fluoride (TbF3) powder with an average particle size of 1.5 to 3μm and anhydrous ethanol are mixed in a ratio of 1kg powder to 2L anhydrous ethanol to form a slurry for standby use; 0.5%*90% / 73.6% of Tb by weight of the magnet is mixed. 73.6 Cr5Si5Al7Cu 9.4 The alloy powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet, and further 0.5%*(1-90%) / 73.6% terbium fluoride (TbF3) powder is evenly sprayed on the two orientation planes of the D10mm*7mm disc magnet;
[0052] The sprayed magnets are neatly stacked in a graphite sintering box. According to the conventional process familiar to technicians, they are kept at 850-940°C for 12-20 hours, and quickly cooled to below 80°C by argon air cooling. The temperature is then raised to 480-540°C and kept for 3-5 hours. They are quickly cooled to below 80°C by argon air cooling to obtain finished magnets. The magnetic properties and corrosion resistance weight loss indicators are shown in Table 1.
[0053] Table 1 Comparison of magnetic properties and weight loss between comparative examples and examples
[0054]
[0055] From Table 1 above, it can be seen that the maximum and minimum coercivity values of Comparative Example 1 differ by 1.1 kOe, which is not conducive to cost reduction. The corrosion resistance of Comparative Example 1 is better than that of the substrate, mainly because the trace elements Cr and Si are innovatively added to the diffusion alloy powder, which improves the corrosion resistance of the magnet surface. Comparative Example 2 has better coercivity dispersion, but very poor corrosion resistance, with a weight loss of 0.71 mg / cm 2, mainly because the fluorine element corrodes the surface of the substrate during the diffusion process, resulting in poor corrosion resistance of the magnet. When X is selected from 0 to 70, the consistency of coercivity is better. The main reason may be that the surface is covered with a layer of fluoride of more than 30%, which plays a good anti-oxidation role. In Examples 4, 5, and 6, when X=50-70, the weight loss of the magnet is relatively good. This is because when X is greater than 50, the first layer of alloy diffuses into the interior of the magnet first, displacing enough light rare earth praseodymium and neodymium to digest the fluorine in the outer layer of fluoride, reducing the corrosion of fluorine on the surface of the substrate and eliminating the adverse effects of fluoride on corrosion resistance.
[0056] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0057] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB, characterized in that: The method comprises the following specific contents: uniformly spraying Dy or / and Tb alloy powder on two orientation planes of a prepared sintered NdFeB magnet, and then uniformly spraying Dy or / and Tb fluoride powder on two orientation planes of the sintered NdFeB magnet after the alloy powder is sprayed, and obtaining the NdFeB magnet product through heat treatment.
2. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB according to claim 1, characterized in that: The amount of the alloy powder is M*m*X% / n, and the amount of the fluoride powder is M*m*(1-X%) / n, wherein M is the total weight of the prepared sintered NdFeB magnet, n is the mass ratio of Dy and Tb elements in the alloy powder used, m is 0.2-1%, and X is 0-70.
3. A method for improving the magnetic consistency and corrosion resistance of NdFeB according to claim 2, characterized in that: m is 0.5%, X is not greater than 70, and the difference between the maximum value and the minimum value of the coercive force of the prepared NdFeB magnet product is less than 0.3 kOe.
4. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB according to claim 2, characterized in that: m is 0.5%, X is not less than 50, and the weight loss of the obtained NdFeB magnet product is less than 0.3mg / cm under the standard conditions of 2.6 atmospheres, 95% humidity, 130℃, and 240h. 2 .
5. A method for improving the magnetic consistency and corrosion resistance of NdFeB according to claim 3 or 4, characterized in that: The alloy powder of Dy and / or Tb is Dy 73.6 Cr5Si5Al7Cu 9.4 or / and Tb 73.6 Cr5Si5Al7Cu 9.4 , with an average particle size of 2 to 8 μm; the fluoride powder of Dy and / or Tb uses DyF3 / TbF3, with an average particle size of 1.5 to 3 μm.
6. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB according to claim 1, characterized in that: The alloy powder and fluoride powder are sprayed in a manner of mixing the powder and anhydrous ethanol in a ratio of 1 kg powder to 2 L anhydrous ethanol to form a slurry and then spraying.
7. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB according to claim 1, characterized in that: The heat treatment comprises neatly stacking the sprayed magnets into a graphite sintering box, keeping the temperature at 850-940° C. for 12-20 hours, rapidly cooling the temperature to below 80° C. with argon, heating the temperature to 480-540° C. again, keeping the temperature for 3-5 hours, and rapidly cooling the temperature to below 80° C. with argon.
8. A method for improving the magnetic properties consistency and corrosion resistance of NdFeB according to claim 1, characterized in that: The preparation steps of the prepared sintered NdFeB magnet include: after being machined into a desired size and shape, cleaning the surface oxide layer, and drying for standby use.